2020
DOI: 10.21203/rs.3.rs-17726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiation of soft tissue and bone sarcomas from benign lesions utilizing 18F- FDG PET/CT-derived parameters

Abstract: Background: Accurate differentiation between malignant and benign in soft tissue and bone lesions is essential for the prevention of excessive pathological biopsy and unplanned surgical resection. However, it remains a challenge and a standard diagnosis modality is urgently needed. The purpose of this study is to evaluate the usefulness of 18F- FDG PET/CT-derived parameters to differentiate soft tissue sarcoma (STS) and bone sarcoma (BS) from benign lesions.Methods: Patients who underwent pretreatment 18F-FDG … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Additionally, Chen et al presented a regression model using SUVmax and a heterogeneity factor (calculated from a metabolism volume-threshold function from 40% to 80%) and found that it showed diagnostic performance superior to that of individual volumetric parameters. [19] Im et al reported that the MTV and TLG obtained using a liver-based threshold (liver SUVmean + 2 SDs) were the parameters with the most statistically significant predictive value for event-free survival (hazard ratios = 11.774 and 13.121, respectively, at posttherapy). [13] We evaluated the MTV and TLG using a liver-based threshold, which would be less influenced by the variability in SUV measurements caused by multiple PET/CT systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Chen et al presented a regression model using SUVmax and a heterogeneity factor (calculated from a metabolism volume-threshold function from 40% to 80%) and found that it showed diagnostic performance superior to that of individual volumetric parameters. [19] Im et al reported that the MTV and TLG obtained using a liver-based threshold (liver SUVmean + 2 SDs) were the parameters with the most statistically significant predictive value for event-free survival (hazard ratios = 11.774 and 13.121, respectively, at posttherapy). [13] We evaluated the MTV and TLG using a liver-based threshold, which would be less influenced by the variability in SUV measurements caused by multiple PET/CT systems.…”
Section: Discussionmentioning
confidence: 99%
“…The volumetric parameters of 18 F-FDG PET/CT (e.g., MTV or TLG) have been introduced to overcome the limitations of the metabolic parameters of 18 F-FDG PET/CT (e.g., SUVmax or SUVpeak), and several studies have published diagnostic values for differentiating malignant from benign bone and soft tissue tumors. [18,19] These studies evaluated the diagnostic performance of the MTV and TLG using various threshold values with a fixed SUVmax of 2.0 or 2.5 or 40%, 50%, and 75% of SUVmax. Additionally, Chen et al presented a regression model using SUVmax and a heterogeneity factor (calculated from a metabolism volume-threshold function from 40% 80%) and found that it showed diagnostic performance superior to that of individual volumetric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The best imaging technique in differentiating benign masses from their malignant counterpart (myxoma vs. myxosarcoma, fibroma vs. fibrosarcoma, angioma vs. angiosarcoma and so on) is PET/CT, which is based on the metabolic activity of the tissues: using 18-Fluorodeoxiglucose ( 18 FDG), a high maximum standardized uptake (SUVmax) and intratumoral glucose metabolic heterogeneity factor (HF) may discriminate well between malignant (sarcomas, lymphomas, or other malignant tumors) and benign masses, as well as in differentiating a tumor thrombus from a simple thrombus. [105][106][107][108][109][110] To improve the sensitivity and specificity of 18 FDG in the particular setting of cardiac tumors, the physiologic glucose uptake by the myocardium must be minimized. This can be obtained with a low-carbohydrate, high-fat diet and with the administration of 50 Units/Kg of body weight of unfractioned heparin before the injection of 18 FDG.…”
Section: Integrating the Echocardiographic Information In A Clinical ...mentioning
confidence: 99%
“…There are weaknesses stemming from discordance between metabolic and volume-based PET-CT parameters. First, SUV max may not accurately reflect the malignant potential of STS and is not a precise indicator of global metabolic activity 51,57 . Because SUV max only reflects the most active part of a tumor, it may not be suitable for a more global assessment of an STS because these tumors show considerable spatial heterogeneity.…”
Section: Limitationsmentioning
confidence: 99%